Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.nicl.2020.102338
|View full text |Cite
|
Sign up to set email alerts
|

Applying surface-based morphometry to study ventricular abnormalities of cognitively unimpaired subjects prior to clinically significant memory decline

Abstract: Highlights A completely automated surface-based ventricular morphometry system. Generate a whole connected 3D ventricular shape model. Test-retest the system in two independent CU subject cohorts. Subregional ventricular abnormalities prior to clinically memory decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 94 publications
(166 reference statements)
0
25
0
Order By: Relevance
“…The MMS measure for brain structures performs well in clinical group comparisons (Dong et al, 2020b, 2019; Li et al, 2016; Shi et al, 2015, 2014b; Wang et al, 2013; Yao et al, 2018), and as we have shown, it has the potential to further be applied for individual Aβ classification. To achieve this goal, we need to solve the challenge that the MMS dimension is usually much larger than the number of subjects, i.e., the so-called high dimension, small sample size problem .…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The MMS measure for brain structures performs well in clinical group comparisons (Dong et al, 2020b, 2019; Li et al, 2016; Shi et al, 2015, 2014b; Wang et al, 2013; Yao et al, 2018), and as we have shown, it has the potential to further be applied for individual Aβ classification. To achieve this goal, we need to solve the challenge that the MMS dimension is usually much larger than the number of subjects, i.e., the so-called high dimension, small sample size problem .…”
Section: Discussionmentioning
confidence: 74%
“…Second, this work only applies hippocampal MMS to predict Aβ positivity. In future work, we plan to introduce more AD risk factors (such as demographic information, genetic information and clinical assessments) (Ansart et al, 2020; Pekkala et al, 2020; Tosun et al, 2014), and more AD regions of interest (ROIs, e.g., ventricles, entorhinal cortex, temporal lobes) (Brier et al, 2016; Dong et al, 2020b; Foley et al, 2017) into our proposed framework; these additional features are expected to improve the Aβ positivity prediction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pekkala et al (2020) use brain MRI measures (volumes of the cortical gray matter, hippocampus, accumbens, thalamus, and putamen) to infer Aβ positivity in cognitively unimpaired (CU) subjects; they achieve a 0.70 area under the receiver operator curve (AUC) with their Disease State Index (DSI) algorithm. Although brain structural volumes are perhaps the most commonly used neuroimaging measures in AD research (Crivello et al, 2010;Reiter et al, 2017;Cacciaglia et al, 2018), surface-based subregional structure measures can offer advantages over volume measures as they contain more detailed and patient-specific shape information (Styner et al, 2004;Thompson et al, 2004;Morra et al, 2009;Qiu et al, 2009;Shen et al, 2009;Apostolova et al, 2010;Costafreda et al, 2011;Younes et al, 2014;Dong et al, 2019Dong et al, , 2020bChing et al, 2020).…”
Section: Introductionmentioning
confidence: 99%